Xiaoyao Pills Prevent Lipopolysaccharide-Induced Depression by Inhibiting Inflammation and Protecting Nerves - Shi, Boyu; Luo, Jie; Fang, Yang; Liu, Xiaobo; Rao, Zhili; Liu, Rong; Zeng, Nan (Frontiers in Pharmacology, 2019)
Lipopolysaccharides are pro-inflammation mediators that can induce inflammation in the serum, hippocampus, and cortex of animals. And lipopolysaccharide-induced neuroinflammatory state resulted in significant depression-like behaviours, including decreased locomotor activity in the open field test, decreased saccharin preference, increased immobility time in the tail suspension test and forced swimming test, decreased comb time in the splash test, and increased latency to food in the novelty suppressed feeding test time, and reduced the levels of neurotrophic factors and synaptic proteins, and decreased Nissl bodies. Treatment with XiaoYao pills ameliorated the depression-like behaviour, decreased the levels of inflammatory indicators, increased those of neurotrophic factors and synaptic proteins, and restored Nissl bodies. Our study suggests that lipopolysaccharides induce inflammation and nerve injury, thereby leading to depression. XiaoYao pills could be considered a potential therapeutic candidate for inflammation-induced depression.